ANALISIS TEKNOLOGI MASJID CIPARI YANG BERGAYA ARSITEKTUR INDO-EROPA - Dimas Seno Bismoko (KALPATARU, 2021)
One of the architectural technologies that developed in the Indonesian Archipelago is known as the "Indische Empire" architecture. This style is a combination of European building forms adapted to the local style buildings, thus giving birth to a mixed architectural form. IndoEuropean architectural technology was initially used for government buildings, but gradually, this art style penetrated other buildings such as residential houses, public facilities, and so on. The Indo-European architectural style is classified as an attempt to find a form of identity for the Dutch East Indies architecture at that time. Cipari Mosque is one of the buildings that use IndoEuropean characteristics in terms of technology. Those are clearly seen from the shape of the building, the material of manufacture and other components that are different from the Javanese mosque in general. Has the technology in the Cipari Mosque removed the general shape of the mosque in Java, so that it has a different shape? Basically, technology only tries to help or make something old become more advanced, new, looks good (physically and aesthetically), efficient and so on, but the form itself depends on the architect who designed it. Not every architect has the same thought in forming a building. The data collection process in this paper uses primary data and secondary data. Primary data was obtained by conducting field observations. Field data used include photos of mosque buildings, measurements, and interviews with mosque managers. Secondary data obtained through literature study, among others, reference books, journal articles, and the internet. The two data sources will be combined to get a complete picture of the data. Salah satu teknologi arsitektur yang berkembang di Nusantara dikenal dengan arsitektur Indische Empire. Gaya ini merupakan perpaduan antara bentuk bangunan Eropa yang diadaptasikan dengan bangunan gaya setempat sehingga melahirkan bentuk arsitektur campuran. Teknologi arsitektur Indo-Eropa awal mulanya digunakan untuk bangunan pemerintahan, tetapi lambat laun gaya seni ini merambah ke bangunan lainya seperti rumah tinggal, fasilitas umum, dan lain-lain. Gaya Arsitektur Indo-Eropa digolongkan sebagai salah satu usaha untuk mencari bentuk identitas arsitektur Hindia-Belanda waktu itu. Masjid Cipari merupakan salah satu bangunan yang menggunakan ciri Indo-Eropa dari segi teknologinya. Hal tersebut jelas terlihat dari bentuk bangunan, bahan pembuatan, dan komponen lainya yang berbeda dengan masjid Jawa umumnya. Apakah teknologi dalam Masjid Cipari telah menghilangkan bentuk umum masjid di Jawa sehingga memiliki bentuk yang berbeda? Dasarnya teknologi hanya mencoba membantu atau membuat sesuatu yang lama menjadi lebih maju, baru, terlihat baik (dari segi fisik maupun estetik), efisien, dan sebagainya. Namun, untuk bentuk itu sendiri tergantung dari arsitek yang merancangnya karena tidak setiap arsitek memiliki pemikiran yang sama dalam membentuk sebuah bangunan. Proses pengumpulan data pada tulisan ini menggunakan data primer dan data sekunder. Data primer diperoleh dengan melakukan pengamatan lapangan. Data lapangan yang digunakan antara lain berupa foto bangunan masjid, pengukuran, serta wawancara terhadap pengelola masjid. Data sekunder diperoleh melalui studi Pustaka, antara lain buku referensi, artikel-artikel jurnal, dan internet. Kedua sumber data tersebut digabungkan untuk mendapatkan gambaran data secara utuh.